(Usborne discovery internet-linked) Mummies & pyramids - Taplin, Sam (Usborne London, 2002)
This series of Internet-linked titles covers a wide range of subjects. Vibrant photography and colourful illustrations combine with lively text and surprising facts to make these books difficult to put down